Rethinking Entrepreneurial Spirit: Why Internal and Social Factors Matter More Than Capital - Hilma Suyana; Syifa Putri Hermawan (SAN Scientific, 2026)
This study examined the effects of self-efficacy, entrepreneurial knowledge, business capital, and family environment on entrepreneurial interest among students. The study involved 163 respondents selected through a questionnaire-based data collection method. Data were analyzed using multiple linear regression, t-tests, and F-tests. The findings reveal that: (1) self-efficacy has a positive and significant effect on entrepreneurial interest; (2) entrepreneurial knowledge has a positive but insignificant effect; (3) business capital has no significant effect; (4) family environment has no significant effect; and (5) simultaneously, all independent variables significantly influence entrepreneurial interest. The originality of this study lies in its finding that internal psychological factors, particularly self-efficacy, play a more dominant role in shaping entrepreneurial interest than external and financial factors such as business capital and family environment. This challenges the conventional assumption in entrepreneurship literature that access to capital and family support are the primary drivers of entrepreneurial intention among students. The managerial implications suggest that educational institutions, governments, and business practitioners should collaborate to create a supportive entrepreneurial ecosystem. Entrepreneurship programs should not only emphasize technical knowledge and financial preparation but also strengthen students' confidence and self-belief to start and manage a business